Consumer protection through prices: an analysis of the energetic sector in European Union countries - Codruţa Mare; Simona Laura Dragoş; Dan Tudor Lazăr; Cristian Mihai Dragoş (Amfiteatru Economic Journal, 2013)
Services of general economic interest (SGEI) are usually offered on markets characterized by monopoly, oligopoly, governmental or local authorities control or other forms of market imperfection. Consequently, issues related to consumer protection also present some particularities. In the energetic sector, the product offered (electricity) is absolutely homogeneous, allowing only consumer protection through price. Our study analyzed the presence of this phenomenon in the 27 countries of the European Union. Data was collected from official institutions, such as the World Bank, Europe's Energy Portal and the National Institutes of Statistics of the member states. Based on OLS regressions we demonstrated the existence of price-based protection for domestic consumers at EU level. Prices are regulated in such a way as to be correlated with the average wage. As an additional argument, we demonstrated that the energy price for industrial consumers follows a different formation mechanism, with main influence factor the energy import dependence.
Keywords: D18; D12; C21; 330; services of general economic interest; consumer protection by price; energy dependence